A Questions Answering System on Hadith Knowledge Graph - Kemas Rahmat Saleh Wiharja; Danang Triantoro Murdiansyah; Muhammad Zakiyullah Romdlony; Tiwa Ramdhani; Muhammad Ramadhan Gandidi (LPPM ITB, 2022)
Several works have presented the Hadith on different digital platforms, ranging from websites to mobile apps. These works were successful in presenting the text of the Hadith to users, but this does not help them to answer any particular questions about religious matters. Therefore, in this work we propose a question-answering system that was built on a Hadith knowledge graph. To interpret the user questions correctly, we used the Levenshtein distance function, and for storing the Hadith in graph format we used Neo4J as the graph database. Our main findings were: (i) a knowledge graph is suitable for representing the Hadith and also for doing the reasoning task, and (ii) our proposed approach achieved 95% for top-1 accuracy.